Plug in battery electric car : design and integration of vehicle front subframe and related systems - Mohamad Arfian Maricar Mohamed Yusoff (2014)
This Final Year Project (FYP) report serves as a documentation for the detailed design and integration of the Plug In Battery Electric Car’s front subframe and its related systems. The author was tasked to modify the steering system, construct the brakes system, analyse the current mounting points of the front subframe and lastly to build a housing for the onboard wireless charger. There are numerous hardware, software and materials which are used in the design of these systems. SOLIDWORKS, CATIA and a personal logbook are amongst the materials used in the conceptual and detailed design stage of this FYP. The author was part of the third batch of final year students attached to this project. The author succeeded in modifying the steering angle required for the vehicle, setting up a mock-up of the brake system which includes bleeding the brake system, analysing the front subframe mounting points and designing a housing for the onboard wireless charger. The author also worked closely with the team members namely, Muhammad Hafiz, Abdul Hafiz and Chua Bee Em. Muhammad Hafiz’s task was to design the chassis which the author had to coordinate for the placement of the steering system. Abdul Hafiz’s task was to design the seating and ergonomics of the car. The author had to coordinate with him regarding the design of the steering system so as to satisfy the ergonomics requirements. Lastly, Chua Bee Em was tasked to design and build the wireless charging system. The author worked with Chua Bee Em in designing the housing for the onboard wireless charger so as to meet the requirements of the wireless charging system.